2015
DOI: 10.1292/jvms.14-0032
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor expression in canine transitional cell carcinoma

Abstract: Transitional cell carcinoma (TCC), a urinary bladder tumor with high mortality, is encountered commonly in dogs. Whereas overexpression of epidermal growth factor receptor (EGFR) is associated with development of human urinary bladder cancer, information on EGFR expression in canine TCC is lacking. In this study, EGFR protein and mRNA expression in canine normal bladder (n=5), polypoid cystitis (n=5) and TCC (n=25) were examined by immunohistochemistry and real-time polymerase chain reaction. EGFR protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
2
27
0
2
Order By: Relevance
“…A statistically significant increase in the EGF level was also observed after the treatment in four dogs with HGE. Our results are similar to other studies (36,38,39) and seem to confirm that EGF plays an important role in tumour development, and that its overexpression correlates with the incidence of tumour relapse in dogs. Thus, EGF can be treated as another prognostic factor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A statistically significant increase in the EGF level was also observed after the treatment in four dogs with HGE. Our results are similar to other studies (36,38,39) and seem to confirm that EGF plays an important role in tumour development, and that its overexpression correlates with the incidence of tumour relapse in dogs. Thus, EGF can be treated as another prognostic factor.…”
Section: Discussionsupporting
confidence: 93%
“…Overexpression of EGF was detected in these cells (37). It is also a neoplastic marker in canine transitional cell carcinoma -TCC (38). In a study on the EGF level in the serum of patients suffering from unresectable hepatocellular carcinoma, a significantly elevated EGF level (784.49 pg/ml) was observed when compared with healthy patients (297.15 pg/ml) or other patients suffering from non-cancerous liver diseases (338.64 pg/ml).…”
Section: Discussionmentioning
confidence: 92%
“…Lapatinib is a tyrosine kinase inhibitor belonging to the 4-anilinoquinazoline class that targets the kinase domain of both HER2 and EGFR. 13,14 Because HER2 and EGFR protein overexpression was observed in more than half of dogs with TCC, 17,20 we aimed to evaluate the potential anti-tumour effects of lapatinib on canine TCC cell lines in this study. Our results showed that lapatinib inhibited growth activity in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, small‐molecule drugs often cross‐react with various species . As EGFR protein overexpression is also observed in 72% of canine TCC, the HER2 and EGFR tyrosine kinase inhibitor lapatinib may be effective in canine TCC.…”
Section: Introductionmentioning
confidence: 99%
“…In canine cancers EGFR overexpression has been reported in canine mammary tumours (CMT), transitional cell carcinomas, medullary thyroid cancer, and gastric epithelial tumours . Gama and colleagues reported EGFR expression to be significantly associated with malignancy but could only report a trend towards reduced disease‐free and overall survival.…”
Section: Introductionmentioning
confidence: 99%